The Role of the Tanjungpinang City Health Office in Environmental Health Supervision of Nutritional Fulfillment Service Units under the Free Nutritious Meals Program: A Case Study of SPPG Mekar Sari - Bayu Setiawan; Eki Darmawan; Khairi Rahmi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Environmental health supervision is an essential component in ensuring food safety and the successful implementation of Indonesia's Free Nutritious Meals Program (Program Makan Bergizi Gratis MBG). This study aimed to examine the role of the Tanjungpinang City Health Office in supervising environmental health at the Nutritional Fulfillment Service Unit (Satuan Pelayanan Pemenuhan Gizi—SPPG), using SPPG Mekar Sari as a case study. A qualitative descriptive approach with a case study design was employed. Data were collected through semi-structured interviews, direct observations, and document analysis involving the Health Office, SPPG management, schools, and community representatives. Data were analyzed using the Miles and Huberman interactive model, while T. Hani Handoko's supervision theory served as the analytical framework. The findings reveal that environmental health supervision has been implemented systematically through four supervisory dimensions: standard setting, performance measurement, performance evaluation, and corrective action. Standardized inspection procedures, periodic environmental health assessments, inter-agency collaboration, and continuous technical guidance have strengthened institutional compliance with sanitation and food safety standards. Corrective actions implemented following supervisory evaluations contributed to improvements in waste management, environmental cleanliness, and hygiene practices. The study concludes that effective environmental health supervision depends not only on regulatory compliance but also on collaborative governance, continuous organizational learning, and adaptive management. These findings provide theoretical contributions to public administration and practical recommendations for strengthening environmental health governance to ensure the sustainability of the MBG Program.